Government Spending and the Income-Expenditure Model: The Multiplier, Spending Composition, and Job Guarantee Programs - Thomas Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper reconstructs the income - expenditure (IE) model to include a distinction between government purchases of output versus government production. The distinction has important consequences for output and employment multipliers. The paper also extends the IE model to incorporate a government job guarantee program (JGP), and the extended model illuminates the automatic stabilizer properties of a JGP. The model is then extended to include Kaleckian income distribution effects. That generates a novel Kaleckian balanced budget multiplier driven by changed composition of government spending. The paper concludes with some economic and political economy concerns about a JGP that are flagged by the model.
Keywords: E10; E12; E62; 330; Government spending; spending composition; balanced budget multiplier; job guarantee program